Clinical Investigations in Gastroenterology - Bateson, Malcolm C.; Bouchier, Ian A.D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The new edition of this book provides a comprehensive review of the basic tests available in gastroenterology. Chapters examine widely-used modern techniques such as ultrasonography for Crohn$1 (Bs disease, capsule endoscopy, elastography and video proctosigmoidoscopy among others. Fully updated to reflect the recent advances in the field in the last 20 years, this volume evaluates investigations for their current clinical usefulness in the management of patients. The reader will benefit from a critical analysis describing those older tests which have proved their worth alongside the newer procedures which have been introduced. Emphasis is placed on these techniques of which the authors have personal experience. The book is designed for trainees and clinicians without special expertise in gastroenterology, as well as being a shelf manual for the gastroenterologist and the staff of gastroenterology investigation units.s
1. Helicobacter pylori -- 2. Upper digestive endoscopy -- 3. Intubation -- 4. Oesophagus -- 5. Stomach -- 6. Small Intestine -- 7. Absorption -- 8. Colon and rectum -- 9. Gastrointestinal bleeding -- 10. Stool examination -- 11. Pancreas -- 12. Liver biochemistry -- 13.Liver biopsy -- 14. Liver imaging and manometry -- 15. Gallbladder and bile ducts -- 16. Ascites and the peritoneum -- Appendix.
Keywords: Medicine; Radiology; Gastroenterology; Medicine & Public Health; Gastroenterology; Imaging / Radiology